2016
DOI: 10.2174/1874325001610010877
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanostructures in Bone Tissue Engineering

Abstract: Background:Recent advances in developing biocompatible materials for treating bone loss or defects have dramatically changed clinicians’ reconstructive armory. Current clinically available reconstructive options have certain advantages, but also several drawbacks that prevent them from gaining universal acceptance. A wide range of synthetic and natural biomaterials is being used to develop tissue-engineered bone. Many of these materials are currently in the clinical trial stage.Methods:A selective literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 235 publications
(269 reference statements)
0
23
0
Order By: Relevance
“…Their applications in the context of BTE have witnessed significant advancements in recent decades, especially when it entered into the 21 st century as indicated by the significantly increased number of publications on this topic ( Figure 4B). [65][66][67][68]…”
Section: Carbon-based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…Their applications in the context of BTE have witnessed significant advancements in recent decades, especially when it entered into the 21 st century as indicated by the significantly increased number of publications on this topic ( Figure 4B). [65][66][67][68]…”
Section: Carbon-based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…A small quantity of carbon nanotubes composed of polymers (<0.5 wt %) can lead to impressive increases in their mechanical properties. Human bones have an average Young's modulus (GPa) of 12–18, hydroxyapatite 95 (GPa), bioglass 35 (GPa) and the multiwalled carbon nanotubes (MWCNTs) between 200 and 1950 GPa . The facility of MWCNTs to enhance cellular adhesion and proliferation has meant that these materials are incorporated into other natural or synthetic materials to fabricate scaffolds for regenerative medicine …”
Section: Introductionmentioning
confidence: 99%
“…Cortical bone is an elastic and plastic substance with tensile strength of 0.051-0.133 gigapascals (GPa) and a Young's modulus of 12-18 GPa. In contrast, MWCNTs have a tensile strength of over 63 GPa and Young's modulus of 200-1950 GPa [82], but its macroscopic strength as a material can change according to the molding technique that is implemented. In our previous study, we demonstrated that blocks made of MWCNTs alone are too soft with porous interiors [51] and too hard without pores [74].…”
Section: Mechanical Properties Of Cntsmentioning
confidence: 99%